Pengaruh Stretching Terhadap Penurunan Nyeri Punggung pada Personel di SPN Polda Jatim - septafani, oktaffrastya widhamurti; Estuningsih, Ririn (Jurnal Kesehatan Holistic, 2025)
One of the efforts that are considered appropriate to prevent an increase in back pain complaints is the provision of stretching training. Design from this result is pre experiment with one group pre post test design. With measure back pain complaints and then given streching during 30 minutes after that measure again back pain complain respondents. This reseach involved 30 repondents, with a total sampling technique of sampling. Before being given treatment, almost all of 30 respondents, 83.3%, or 25 respondents complained of controlled severe pain, while a small proportion of respondents, 17% or 5 respondents, complained of moderate pain. After being given treatment, almost all of 30 respondents, 83% or 25 respondents, complained of moderate pain and 5 respondents, a small percentage of 17% or 5 respondents complained of mild pain.